THE INFLUENCE OF WORK ETHICS AND WORK PROFESSIONALISM ON PERFORMANCE AT PT. BRI BRANCH SINGAMANGARAJA MEDAN - Reza Nurul Ichsan; Lukman Nasution; Dedi Setiadi (Jurnal Darma Agung, 2022)
This study aims at determining the influence of work ethics and work professionalism on work performance in the company PT. BRI Branch Office Sisingamangaraja Medan. The population of this study is all employees who are in the office environment of PT. BRI Sisingamangaraja Branch in Medan with 77 employees. This is quantitative research with an explanatory approach. The research instrument used was the distribution of questionnaires to employees at the BRI Sisingamangaraja Branch Office in Medan. Based on the results of this study, the following results were obtained: (1) work ethic has a significant effect on work performance. This can be seen from the value of tcount at X1 = 2,946 > ttable (0,05;77) = 1,991; (2) work professionalism has a significant effect on work performance. This can be seen from the value of tcount at X2 = 2,355 > ttable (0,05;77) = 1,991